2007
DOI: 10.2166/wst.2007.487
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of a wine distillery wastewater using white rot fungi and the subsequent production of laccase

Abstract: The aim of this work was to ascertain whether a submerged culture of a white rot fungus could be used to treat distillery wastewater, and whether the compounds present in the wastewater would stimulate laccase production. Trametes pubescens MB 89, Ceriporiopsis subvermispora, Pycnoporus cinnabarinus and UD4 were screened for their ability for the bioremediation of a raw, untreated distillery wastewater as well as distillery wastewater that had been pretreated by polyvinylpolypyrrolidone. Suitability of each st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…The concentration of phenolic compounds increased slightly by the end of the fungal treatment, which indicated that a phenolic compound was synthesised during the fungal treatment. This had also occurred with the treatment of distillery wastewaters (Strong & Burgess, 2007). Eggert et al (1996) identified a tryp-tophan-derived metabolite (3-hydroxyanthranilate) that was secreted by Pycnoporus cinnabarinus, which functioned as a mediator and allowed laccase to oxidise substances with higher oxidation potentials.…”
Section: Degradation Of Phenolic Compoundsmentioning
confidence: 97%
See 2 more Smart Citations
“…The concentration of phenolic compounds increased slightly by the end of the fungal treatment, which indicated that a phenolic compound was synthesised during the fungal treatment. This had also occurred with the treatment of distillery wastewaters (Strong & Burgess, 2007). Eggert et al (1996) identified a tryp-tophan-derived metabolite (3-hydroxyanthranilate) that was secreted by Pycnoporus cinnabarinus, which functioned as a mediator and allowed laccase to oxidise substances with higher oxidation potentials.…”
Section: Degradation Of Phenolic Compoundsmentioning
confidence: 97%
“…7). The treatment of a brandy distillery wastewater had previously yielded laccase concentrations of 4 644 ± 228 units/L in shakeflask cultures (Strong & Burgess, 2007).…”
Section: Laccase Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi are capable of degrading these compounds or using them as a carbon and energy source. Fungal digestion of wine distillery wastewaters using Trametes pubescens MB 89 has been shown to remove a large portion of the total phenols, COD, colour, increase the pH and produce a high concentration of laccase (Strong and Burgess 2007). Laccase, one of the major fungal enzymes, is a phenoloxidase that can be obtained in high concentrations from fungal cultures.…”
Section: Introductionmentioning
confidence: 99%
“…This group of microorganisms is capable of completely degrading polymers of phenolic origin, including lignin. The biodegradation activity toward some wide spread phenolic pollutants is studied together with the laccase production and expression of phenol oxidase activities in general [4,20]. Lignin degradation by white-rot fungi is known as a cometabolic process, and growth of white-rot fungi on monoaromatics (constituents of the lignin macromolecule) have only rarely been described [3].…”
Section: Introductionmentioning
confidence: 99%